Rotator Cuff Repair With a Bioinductive Patch - Brian Forsythe MD; Derrick M. Knapik MD; Harsh H. Patel BA; Elyse J. Berlinberg BS; Jorge Chahla MD, PhD; Michael T. Freehill MD; Jon Riboh MD (SAGE Publishing, 2022)
Background: As a degenerative condition, symptomatic rotator cuff disease is frequently seen in the aging population, often requiring arthroscopic repair to eliminate pain and restore function. Repair integrity remains a concern in both short- and long-term postoperative periods due to high rates of primary repair failures, leading to increased interest in biologic patch augmentation to improve healing. Indications: Patch augmentation during rotator cuff repair is indicated in patients at high risk for repair failure or incomplete healing, including patients with poor quality, degenerative tendon tissue, those undergoing revision repair, and patients with large or massive rotator cuff tears. Technique Description: Standard arthroscopic portals are established and following diagnostic arthroscopy, the rotator cuff tear is identified, mobilized, and the humeral head gently debrided to a bleeding surface. Medial row suture anchors are placed, and following suture passage through the rotator cuff, the medial row sutures are tied. A bioinductive augmentation patch is introduced and provisionally secured medial to the enthesis utilizing spinal needles. Sutures are shuttled over the patch and incorporated into the lateral row repair utilizing 2 knotless suture anchors, effectively securing the patch over the bone-tendon interface. Results: Utilization of the described patch augmentation technique may improve repair healing by stimulating collagen formation and tissue vascularity, while providing structural support during the immediate postoperative period, effectively facilitating new tissue formation. Discussion/Conclusion: Incorporation of the bioinductive patch into the lateral row suture repair, directly over the tendon-bone interface, may assist in repair healing and decrease issues related to patch migration, while minimizing operative time and materials cost.